CASSIB : Central Asia & Siberia Specialized Information Service (2020)
Webseite des Fachinformationsdienstes (FID) Zentralasien an der Niedersächsischen Staats- und Universitätsbibliothek Göttingen. Auf dieser Webseite werden Informationen über die zentralasiatischen und sibirischen Turkvölker, mongolischen, tungusischen und paläoasiatischen Völker gegeben, sowie Forschungsprojekte, Digitalisierungsvorhaben aus der Region vorgestellt. Aktuelle Informationen zu Konferenzen und Publikationen etc. werden ebenfalls geboten. - Website of the Specialised Information Service for Central Asia and SIberia (FID) at the Göttingen State and University Library. This website provides information about the Central Asian and Siberian Turkic, Mongolian, Tungusian and Palaeoasiatic peoples, as well as research and digitization projects from the region. Current information on conferences and publications etc. is also provided.